2003
DOI: 10.1007/s00134-003-1681-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatal air embolism in an extremely low birth weight infant: can it be caused by intravenous injections during resuscitation?

Abstract: The average amounts of air which had entered the closed system after 100 acts of syringe assembly and aqua administration were 1.84, 1.95, and 2.0 ml. This corresponds to an average volume of almost 0.02 ml per injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Air embolism in neonates and young infants due to peripheral intravenous infusion is exceedingly rare. We find only seven documented cases in the English-language literature (17)(18)(19)(20)(21). Only one of those involved a previously healthy infant as in this case (18).…”
Section: Discussionmentioning
confidence: 78%
“…Air embolism in neonates and young infants due to peripheral intravenous infusion is exceedingly rare. We find only seven documented cases in the English-language literature (17)(18)(19)(20)(21). Only one of those involved a previously healthy infant as in this case (18).…”
Section: Discussionmentioning
confidence: 78%
“…27,28 In premature infants, SAE is always due to respiratory-assisted ventilation, such as insertion of central venous lines, 12,28 intravenous injections during resuscitation, 22 and, most of all, long-standing mechanical high-pressure ventilation. [1][2][3][4][5][6][7][8][9][10][11]19,21,22,29 Moreover, it has also been reported in one full-term infant suffering from Figure 2 The first chest-abdomen X-ray taken (A) shows bilateral lung opacities, partially hyperlucent right-lower lobe, tip of the umbilical venous catheter slightly bent to the right above the diaphragm, and signs of free air within the liver. The second chest-abdomen X-ray (B) shows left pneumothorax, diffuse interstitial emphysema, and free air in hepatic, iliac, femoral, and popliteal veins as well as in the upper-arm veins and, bilaterally, the jugular veins.…”
Section: Discussionmentioning
confidence: 99%
“…Both SAE and pulmonary vein air embolism are rare, [1][2][3][4][5][7][8][9][10][11][12][13][18][19][20][21][22][23] and there are only a few reported patients who have survived these usually fatal complications. 4,5,18 In the surviving case reported by Kogutt, the patient had no clinical symptoms and the diagnosis was based on radiographic findings only, 4 and an infant with such a condition treated by Weiner et al survived 13 days.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization of air is also a consideration with IO infusions, just as with PIV and CVC infusion (Wald et al, 2003). Anatomic studies by Tarrow showed that air emboli are usually caught in the capillaries of the sternum during sternal infusion.…”
Section: Complicationsmentioning
confidence: 99%